Photocatalytic heterostructures-based BiFeO3embedded liquid natural rubber (LNR) for highly removal of cationic dye under direct sunlight - Ridzuan, N.D.M. (Elsevier Ltd, 2020)
In this study, the composite consists of bismuth ferrite (BiFeO3) photocatalyst embedded into macroporous liquid natural rubber (LNR) matrices was fabricated to assess the removal efficiency of methylene blue (MB) dye under direct sunlight. The structural properties and morphology of LNR-BiFeO3 composite were thoroughly characterised using spectroscopic and microscopic methods. X-Ray diffractogram of the composite demonstrated successful inclusion of BiFeO3 into the LNR network. During solar-driven photocatalytic activity of LNR-BiFeO3, the effects of selected operating parameters on removal efficiency, such as catalyst dose, irradiation time, initial dye concentration, and solution pH, were determined. At optimum catalyst dose (0.15 g BiFeO3) and irradiation time (3 h), degradation of 10 ppm MB was remarkably efficient as 98.9+ 0.09 have been successfully discarded from the system. The composite had managed to degrade up to 75 ppm MB with degradation efficiency exceeding 89.0 . In order to investigate the mechanism of MB removal using LNR-BiFeO3, monitoring of removal mode, kinetics and scavenger study were carried out. The outcomes revealed that MB removal did fit well with Langmuir-Hinshelwood kinetic model, in which BiFeO3 (Ebg = 1.76 eV) is responsible for photodegradation process using OH-, O2- and h+ with assistance of adsorption by the composite. The composite could be reused for five cycles without any post-treatment or separation step, and most importantly, no significant loss noted in its activity. This eco-friendly and economical approach will render new opportunities for this advanced photocatalyst as great potential in environmental remediation for wastewater treatment. Â© 2020 Elsevier Ltd.